The Theology of God’s Oneness (Tawḥīd) in Munaǧǧā ibn Ṣadaqah’s Thought - F. O. Nofal (Концепт: философия, религия, культура, 2025)
The article deals with the philosophical and religious study of the Samaritan concept of al-tawḥīd — “the oneness of God” and is based on the “Book of Differences [between Jews and Samaritans]” (Kitāb al-H̱ ilāf), composed by Munaǧǧā ibn Ṣadaqah al-Sāmirrī, also known as “the Son of the Poet” (Ibn Šāʿir). The relevance of the study is due to the both the unexplored theological systems of the Samaritan writers’ legacy and their connection with the Muslim tradition. Munaǧǧā, as a Samaritan thinker of 12th – 13th centuries, followed Arab-Muslim discourse in his teachings; this was no exception in the field of theology, Muʻtazili’, Ashʻari’ and Maturidi’ versions of which became widespread in Samaritan circles as well as Peripatetic metaphysics. Munaǧǧā considers al-tawḥīd theory in its Muslim aspects — tawḥid al-ḏāt (“the oneness of Divine Substance”), tawḥid al-ṣifāt (“the oneness of Divine Attributes”) and tawḥid al-afʿāl (“the oneness of Divine Action”). “The oneness of Divine Substance” means an absolute numerical and qualitative uniqueness of God in His essence; Munaǧǧā proves it by Mutazilite arguments, directed against dualistic doctrines of East. Another impact of Mutazili’ thought is obvious in tawḥid al-ṣifāt concept, which requires, according to Munaǧǧā, the ontological equivalence of Divine Essence to His attributes; this kind of equivalence makes any multiplicity in God’s eternal and unchangeable Substance impossible. “The oneness of Divine Action” explains the connection between God and world’s variability. Since God is the Actor par excellence, all created actions belong to Him — as Munaǧǧā notes, universally and particularly; in this case, the Samaritan theologist adapts Maturidi’ concept of al-kasb, “appropriation”: human appropriates created, in accordance to his free will, action through created might (qudrah). The impact of Arab Peripatetic philosophy on Munaǧǧā’s theology is evident from his use of terms “necessary — possible” (wāǧib — mumkin); at the same time Munaǧǧā criticizes peripatetic theory of emanation and universal nature of Divine Knowledge and Might. In conclusion the author compare Munaǧǧā’s theological concepts with relevant teachings of ʾAbū al-Ḥasan al-Ṣūrī stated in “the Book of Slaughter” (Kitāb al-Ṭabbāẖ) — the first speculative work of Samaritans. Finding that while Ibn Šāʿir adopts a kalamic-peripatetic synthesis, merging terms used in both traditions, relying on Muʻtazili’ ʼ theology of attributes and Maturidiʼ anthropology, al-Ṣūrī follows the philosophy of kalam in its natural and theological themes, rejecting the concept of emanation and the division of intelligibilia into universal and particular. This article continues the work of its author on Kitāb al-H̱ ilāf, the first part of which was published in 2024.